Impacts of Stocking Density on Broiler Chicken Performance Stress Reaction and Mortality in Broiler Chicken - Chauhan, Pankaj; Singh, Kunwar Dhananjay; Pramanik, Partha Sarathi; Kumar, Subodh; Srivastav, Ashish Kumar; Tripathi, Krishna Kant; Nandan, Durgesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
tThe present study investigated the effect of stocking density on growth performance, stress reaction, and mortality in broiler chickens. Two hundred and forty (240) day-old straight run commercial broiler chicks (Vencob) were divided into two batches having 120 chicks each and further subdivided into three equal groups (G1, G2, G3) representing different stocking densities (20, 25, and 30-meter square/bird) having 40 chicks in each group. It was evident that, after the 2nd week, body weight gain of G3 group was significantly (p
Keywords: Body weight; Body weight gain; Broilers; Feed conversion ratio; Heterophil-lymphocyte ratio